Techno-economic analysis of calcium looping processes for low CO2 emission cement plants. (March 2019) - De Lena, Edoardo; Spinelli, Maurizio; Gatti, Manuele; Scaccabarozzi, Roberto; Campanari, Stefano; Consonni, Stefano; Cinti, Giovanni; Romano, Matteo C.
Highlights: Tail-end and integrated Calcium looping configurations assessed. All CaL configurations involve significant fuel consumption, especially tail-end CaL. Heat recovery steam cycle compensates the electric absorption of ASU and CPU. Cost of cement increase: +67% and +74% for tail-end and integrated cases respectively. Cost of CO2 avoided: 52 €/t and 58.6 €/t for tail-end and integrated cases respectively. Abstract: The scope of this work is to perform a techno-economic analysis of two Calcium Looping processes (CaL) for CO2 capture in cement plants. Both tail-end CaL system with fluidized bed reactors and integrated CaL system with entrained flow reactors have been considered in the analysis. The calculation of the heat and mass balances and the economic analysis are consistent with the methodology defined in the framework of the H2020 Cemcap project. The analysis shows that the assessed CaL systems (especially the tail-end configuration) involve a significant increase of fuel consumption compared to a reference cement kiln without carbon capture. However, a large part of this additional energy input is exploited in a heat recovery steam cycle, which generates the electric power required to satisfy the consumption of the CO2 capture auxiliaries (i.e. the power absorbed by the air separation and CO2 compression and purification units). The integrated CaL process features a lower rise of equivalent fuel consumption (+59% compared to the reference) and a larger reduction of direct CO2 emission (-93% compared to the reference). The specific primary energy consumption for CO2 avoided (SPECCA), which takes into account also the indirect fuel consumption/savings and indirect emissions/avoided emissions due to electricity exchange (import/export) with the grid, ranges between 3.17–3.27 MJLHV /kgCO2 for the integrated system vs. 3.76–4.42 MJLHV /kgCO2 for tail-end cases, depending on the scenario considered for the grid electricity mix. The economic analysis highlights that CaL processes are capital intensive, which involve, roughly, a doubling of the Capex of the whole cement plant with CCS compared to a greenfield conventional cement plant. However, the obtained cost of CO2 avoided is competitive with alternative technologies and ranges between about 52 €/tCO2 of the tail-end configuration and 58.6 €/tCO2 of the integrated one.